Evaluation of clinical efficacy of continuous care with improved insulin injection techniques on patients with diabetes mellitus: a randomized controlled trial. Issue 6 (June 2022) - Zhang, Fang-Ying; Shen, Mengyuan; Sun, Li-Qin
Objective: To investigate the clinical effect of continuous care with improved insulin injection techniques on patients with diabetes mellitus. Methods: This randomized controlled trial enrolled patients with diabetes mellitus. They were randomly assigned to a control or observation group. Patients in the control group received conventional continuous nursing. Patients in the observation group were given optimized insulin injection education and continuous nursing on the same basis as the conventional nursing used in the control group. Blood glucose-related outcomes, knowledge of insulin injections and adverse events were recorded. Results: A total of 96 patients with diabetes mellitus were enrolled in the study ( n  = 48 per group). There were no significant differences between the two groups in terms of sex, age and glycosylated haemoglobin (HbA1c ). Compared with the control group, continuous care combined with optimized insulin injection techniques significantly reduced blood glucose target time, fasting blood glucose, 2-h postprandial blood glucose and HbA1c . The proportions of patients reporting a subcutaneous mass, insulin leakage and hypoglycaemic events were significantly lower in the observation group; and pain scores were significantly reduced compared with the control group. Conclusions: Continuous care and optimization of insulin injection techniques can help patients achieve better diabetes-related outcomes. Study Registration Number: ChiCTR2200057166.